Cellular and Mitochondrial Pathways Contribute to SGLT2 Inhibitors-mediated Tissue Protection: Experimental and Clinical Data - Sanz, Raúl Lelio; Menéndez, Sebastián Garcia; Inserra, Felipe; Ferder, León; Manucha, Walter (Current Pharmaceutical Design, 2024)
In metabolic syndrome and diabetes, compromised mitochondrial function emerges as a critical driver of cardiovascular disease, fueling its development and persistence, culminating in cardiac remodeling and adverse events. In this context, angiotensin II - the main interlocutor of the renin-angiotensin-aldosterone system - promotes local and systemic oxidative inflammatory processes. To highlight, the low activity/expression of proteins called sirtuins negatively participates in these processes, allowing more significant oxidative imbalance, which impacts cellular and tissue responses, causing tissue damage, inflammation, and cardiac and vascular remodeling. The reduction in energy production of mitochondria has been widely described as a significant element in all types of metabolic disorders. Additionally, high sirtuin levels and AMPK signaling stimulate hypoxia-inducible factor 1 beta and promote ketonemia. Consequently, enhanced autophagy and mitophagy advance through cardiac cells, sweeping away debris and silencing the orchestra of oxidative stress and inflammation, ultimately protecting vulnerable tissue from damage. To highlight and of particular interest, SGLT2 inhibitors (SGLT2i) profoundly influence all these mechanisms. Randomized clinical trials have evidenced a compelling picture of SGLT2i emerging as game-changers, wielding their power to demonstrably improve cardiac function and slash the rates of cardiovascular and renal events. Furthermore, driven by recent evidence, SGLT2i emerge as cellular supermolecules, exerting their beneficial actions to increase mitochondrial efficiency, alleviate oxidative stress, and curb severe inflammation. Its actions strengthen tissues and create a resilient defense against disease. In conclusion, like a treasure chest brimming with untold riches, the influence of SGLT2i on mitochondrial function holds untold potential for cardiovascular health. Unlocking these secrets, like a map guiding adventurers to hidden riches, promises to pave the way for even more potent therapeutic strategies
Keywords: SGLT2i